A retrospective investigation of the effect of tranexamic acid application and tourniquet duration on postoperative bleeding amount in patients undergoing total knee arthroplasty - Karaca, Mustafa Onur; Merter, Abdullah; Başarır, Kerem; Güzel, Mehmet Bahaddin (The European Research Journal, 2022)
Objectives: It is aimed to investigate the effect of tourniquet and tranexamic acid (TXA) on the amount of perioperative bleeding in patients undergoing total knee arthroplasty. Methods: One hundred and ninety-three patients included in the study. The patients included in the study were divided into 4 groups. Group 1 (n = 78) was determined as the patient group with long-term tourniquet application, but without additional application and was accepted as the control group. Group 2 (n = 40) was the long-term tourniquet and intravenous (IV) TXA applied group, Group 3 (n = 40) was the long-term tourniquet and intra-articular TXA applied group, and Group 4 (n = 35) was the short-term tourniquet (only in the cementing phase) and IV TXA applied group. The difference between groups according to use of a tourniquet during the operation, the method and dose of TXA, the amount of postoperative blood transfusion, the amount of drained blood, the length of hospital stay, and complications were investigated. Results: The largest Hemoglobin (Hb) and Hematocrit (Hct) decreases were found in Group 1 (3.39 ± 0.92 g/dl and 10.8%, respectively). Also the highest drainage (median 350 ml), transfusion (16.7%), length of hospital stay (mean 4.51 ± 1.07 days) and estimated blood loss (median 1559.8 ml) were in Group 1 (p < 0.05). The lowest Hb decrease (mean 2.95 ± 0.68 g/dl) and lowest drainage (median 150 ml) was seen in group 3 and the lowest length of hospital stay (mean 3.89 ± 0.8 days) in group 4 (p < 0.05). Conclusions: The use of TXA was shown to lead to a reduction in Hb and Hct, the amount of blood drained after surgery, and the length of hospital stay. The use of TXA may be a good option for bleeding control in patients undergoing total knee arthroplasty.